Conceptual bases of administrative-delictual production in field of occupational of the cultural heritage - Пивовар, Ірина Вікторівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article investigates the category of administrative-delictual proceedings in the sphere of cultural heritage protection, and formulates general and specific features. The relevance of the article be determined in insufficiently settlement of administrative-legal support in the sphere of cultural heritage protection and theoretical-administrative elaboration are characterized by inconsistency in this sphere. Basing on the the theoretical sources and national legislation аuthor the article delimits categories «the administrative-delictual proceedings» and «proceedings in cases of administrative offenses». The author defines such general features of administrative-delictual proceedings in the sphere of cultural heritage protection official, state-imperious character; is regulated by the rule of law; it is based on «administrative-coercive activity»; goal orientation; legal character; еxternal forced mental and/or physical impact on the consciousness and behavior of certain actors in the field; specific features: special sphere of regulation of public relations for the implementation of administrative-coercive activity - sphere of cultural heritage; personified character; the lack of official subordination between subjects authorized to operate within an administrative tort of production in the field of cultural heritage, and those for which they are carried out; the specific legal nature of the grounds of its occurrence. On the basis of the conducted private definition of concepts «administrative-delictual proceedings in the sphere of cultural heritage protection» is formulated, recommendations, directed on perfection of law bases of application of measures of administrative compulsion of investigated sphere, are expressed. In particular the such a production is a set of procedural actions authorized officials as defined in the law and aimed at preventing, combating administrative offenses, providing administrative delictual proceedings, prosecution of perpetrators and the application of administrative recovery measures in the field of cultural heritage.